2013
DOI: 10.1186/1475-2840-12-44
|View full text |Cite
|
Sign up to set email alerts
|

Early cardiac changes in a rat model of prediabetes: brain natriuretic peptide overexpression seems to be the best marker

Abstract: BackgroundDiabetic cardiomyopathy (DCM) is defined as structural and functional changes in the myocardium due to metabolic and cellular abnormalities induced by diabetes mellitus (DM). The impact of prediabetic conditions on the cardiac tissue remains to be elucidated. The goal of this study was to elucidate whether cardiac dysfunction is already present in a state of prediabetes, in the presence of insulin resistance, and to unravel the underlying mechanisms, in a rat model without obesity and hypertension as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
61
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 65 publications
4
61
0
2
Order By: Relevance
“…As cardiac hypertrophy is an important feature of diabetic cardiomyopathy (DCM) (Nunes et al 2013), we speculate that perigestational exposure to HFA may program female progeny to develop DCM, increasing the risk of heart failure (Boudina & Abel 2010, Nunes et al 2013. Strikingly, hyperglycemia (Murarka & Movahed 2010), hyperinsulinemia (Boudina & Abel 2010, Murarka & Movahed 2010, and adiponectin deficiency (Guo et al 2013), all manifested in HFA female offspring, have been suggested to contribute to cardiac hypertrophy (Guo et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As cardiac hypertrophy is an important feature of diabetic cardiomyopathy (DCM) (Nunes et al 2013), we speculate that perigestational exposure to HFA may program female progeny to develop DCM, increasing the risk of heart failure (Boudina & Abel 2010, Nunes et al 2013. Strikingly, hyperglycemia (Murarka & Movahed 2010), hyperinsulinemia (Boudina & Abel 2010, Murarka & Movahed 2010, and adiponectin deficiency (Guo et al 2013), all manifested in HFA female offspring, have been suggested to contribute to cardiac hypertrophy (Guo et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the impact of the HSu diet on leptin serum levels and on leptin receptor expression would be of interest. Overall, our study shows that nine week of HSu-diet, which mimics at least in part Western diets [10,11,47], can lead to impaired hepatic glucose and lipid metabolism, typical features of T2DM, already present in this prediabetic model, even in the absence of obesity. This animal model of diet-induced prediabetes shows reduced glucose tolerance, postprandial hyperglycemia, hyperinsulinemia, reduced insulin sensitivity (resistance), and hypertriglyceridemia, together with impaired gluconeogenesis and lipogenesis ( Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that increased oxidative/nitrative stress coupled to the activation of various downstream proinflammatory and cell death pathways plays pivotal roles in the development of complex biochemical, mechanical and structural alterations that are associated with DCM [33, 34]. However, despite this accumulated knowledge, treatments for DCM remain poor.…”
Section: Discussionmentioning
confidence: 99%